Agritourism Transforming farmers and changing communities - Cabigas-Sy, Charmielyn Villanueva (Quezon City Asian Center, University of the Philippines Diliman, 2019)
"Agricultural assets when coupled with tourism services and experiences bring additional benefits that augment farm income and maintain business viability. Studies have established that agritourism offers an alternative business strategy that brings myriad of value not just to farm owners, but to the local community and state economy as well. However, these researches focused on the contributions of agritourism in the national level. Moreover, there is lack of materials most especially in the Philippines that looks into the motivations of farm owners to engage in agritourism, the transformations that transpired and the outcomes these changes brought about. Guided by McLennan's transformational theory and drawing on studies of other agritourism researches, this study hoped to cover such grounds. Findings established that changes occur over time covering spaces, structures, and institutions. This study aimed to bridge the gap in understanding the changes occurring at firm level and the benefits it brought to the community within which it operates"--Author
Thesis
Keywords: Agritourism -- La Union, Philippines; Farms -- Recreational use -- La Union, Philippines; Rural development -- La Union, Philippines